The Legal Protection Against Child Marriage in Indonesia - Rizky Irfano Aditya; L.B. Waddington (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2021)
Every child is a human being who possesses the right to justice, freedom, and opportunity to develop regardless of nationality, race, religion, or skin complexion. These rights of children are guaranteed by the United Nations Universal Declaration of Human Rights. However, its reality indicates otherwise, as children are often the victims of exploitation. One of the worst such kinds of child exploitation is child marriage. This study aims to analyze the legal protection against child marriage in Indonesia. This research is conducted through the normative analysis of various written sources. This study concludes that the Indonesian Child's Act even has a provision that stipulates the obligation of parents to prevent early marriages. However, the law is somewhat effective in Indonesia. Unfortunately, the fatal flaw is the low-threshold provision that enables parents to request dispensation for early marriage. This shatters all the efforts to eliminate child marriage. Thus far, the Indonesian Government also has shown its reluctance to ever amend discriminatory provisions in the Indonesian Marriage Act related to the practice of child marriage despite numerous recommendations from the Convention on the Elimination of Discrimination against Women.